2017
DOI: 10.1016/j.jtcme.2016.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological properties of Salvia officinalis and its components

Abstract: Salvia officinalis (Sage) is a plant in the family of Labiatae/Lamiaceae. It is native to Middle East and Mediterranean areas, but today has been naturalized throughout the world. In folk medicine, S. officinalis has been used for the treatment of different kinds of disorders including seizure, ulcers, gout, rheumatism, inflammation, dizziness, tremor, paralysis, diarrhea, and hyperglycemia. In recent years, this plant has been a subject of intensive studies to document its traditional use and to find new biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
368
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 469 publications
(389 citation statements)
references
References 92 publications
15
368
0
6
Order By: Relevance
“…2,3 Lamiaceae species have been used in traditional medicine for the treatment of depression, headache, asthma, 4 stress, 5 and respiratory 6 and Alzheimer's diseases. 7,8 In addition, these plants have antioxidant, 9 antiallergic, 10 antimicrobial, 11 anticarcinogenic, 12 anti-inflammatory, 13 astringent, 14 and antiHIV-1 effects. 15 These properties are mainly due to phenolic compounds found in the plants, especially rosmarinic acid (RA).…”
mentioning
confidence: 99%
“…2,3 Lamiaceae species have been used in traditional medicine for the treatment of depression, headache, asthma, 4 stress, 5 and respiratory 6 and Alzheimer's diseases. 7,8 In addition, these plants have antioxidant, 9 antiallergic, 10 antimicrobial, 11 anticarcinogenic, 12 anti-inflammatory, 13 astringent, 14 and antiHIV-1 effects. 15 These properties are mainly due to phenolic compounds found in the plants, especially rosmarinic acid (RA).…”
mentioning
confidence: 99%
“…In another examination, it has been reported that some chemicals of SO including carnosic acid, carnosol, rosmanol and caffeic acid are responsible for the free radical scavenging activity of SO [33]. The most effective antioxidant constituents of SO are carnosol, rosmarinic acid, and carnosic acid, followed by caffeic acid, rosmanol, rosmadial, genkwanin, and cirsimaritin [34]. The radical scavenging effect of carnosol is comparable to that of α-tocopherol [35].…”
Section: Neuroprotective Effectmentioning
confidence: 97%
“…Some unwanted gastrointestinal side effects have been reported after prolonged use or following overdose of ethanolic extract and volatile oil of SO [34]. However, precautions should be taken regarding its (uncontrolled) usage due to the varying levels of thujones [39].…”
Section: Adverse Effectsmentioning
confidence: 99%
“…A harmadik táblácska, amely nincs kilyukasztva, két gyógynövényt mutat be: a fekete nadálytő gyökerét (Sym phytum officinale, radix), mely tapaszként sebek és égések kezelésére alkalmas, valamint ízületi bántalmakra, és az orvosi zsályát (Salvia officinalis), amely antimikrobiális, gyulladáscsökkentő és fájdalomcsillapító hatású összetevőket tartalmaz [19]. A táblácskán látható még egy kecske, amely a honoráriummal lehetett kapcsolatos.…”
Section: A Tatárlakai Agyagtáblák: Az Első Orvosi éS Gyógyszerészeti unclassified